The Influence of Social Media on Language and Culture Change among the Young Generation - Safar, Muh.; Rosalia, Olyvia; Firayani, Firayani (PT. Anagata Sembagi Education, 2025)
This study examines the impact of social media on language and cultural changes among young generations. The research aims to analyze how the intensity of social media usage influences the emergence of slang, abbreviations, and borrowed words in daily communication, as well as how it accelerates the adoption of foreign cultural trends, shaping social norms and lifestyles. Using a quantitative approach, data were collected from 190 respondents through structured questionnaires. Several statistical tests, including validity, reliability, normality, multicollinearity, multiple regression, t-test, and ANOVA (F-test), were conducted to evaluate the relationships between variables. The findings reveal that social media significantly influences both language and cultural changes, with all tested hypotheses being statistically significant (p < 0.05). The regression model explains 56% of the variation in language and cultural changes (R² = 0.560). These results suggest that while social media fosters linguistic creativity and global cultural exposure, it may also contribute to the erosion of formal language use and local traditions. The study emphasizes the need for balanced digital literacy programs and cultural preservation efforts to mitigate potential negative impacts. Future research should explore long-term effects and additional influencing factors beyond social media.